1998
DOI: 10.1021/ic980574t
|View full text |Cite
|
Sign up to set email alerts
|

Trigonal Bipyramidal M2Ch32- (M = Sn, Pb; Ch = S, Se, Te) and TlMTe33- Anions:  Multinuclear Magnetic Resonance, Raman Spectroscopic, and Theoretical Studies, and the X-ray Crystal Structures of (2,2,2-crypt-K+)3TlPbTe33-·2en and (2,2,2-crypt-K+)2Pb2Ch32-·0.5en (Ch = S, Se)

Abstract: The series of group 14 metal trigonal bipyramidal anions has been extended to the mixed group 13/group 14 metal TlMTe(3)(3)(-) anions (M = Sn, Pb), obtained by the reaction of Tl(2)M(2)Te(3) and K(2)Te in en or in en/ethylamine mixtures and a stoichiometric excess of 2,2,2-crypt with respect to K(+). The thallium anions were characterized in solution by (119)Sn, (205)Tl, (207)Pb, and (125)Te NMR spectroscopy. The small magnitudes of the relativistically corrected reduced coupling constants, (1)(K(M)(-)(Ch))(RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…We have previously shown that density functional theory 39-43 can be used to calculate the geometries and the vibrational frequencies of classically bonded anions of the heavy main group elements. 44,45 In the present study, DFT calculations provide fully optimized geometries and definitive vibrational assignments for the Sn 4 Ch 10 4-(Ch ) Se, Te) anions. The calculated geometries (Table 4) are in good agreement with the experimental ones (Table 2) and reproduce experimental trends, with the Sn-Ch t bonds ∼0.1 Å shorter than the SnCh b bonds.…”
Section: Resultsmentioning
confidence: 97%
“…We have previously shown that density functional theory 39-43 can be used to calculate the geometries and the vibrational frequencies of classically bonded anions of the heavy main group elements. 44,45 In the present study, DFT calculations provide fully optimized geometries and definitive vibrational assignments for the Sn 4 Ch 10 4-(Ch ) Se, Te) anions. The calculated geometries (Table 4) are in good agreement with the experimental ones (Table 2) and reproduce experimental trends, with the Sn-Ch t bonds ∼0.1 Å shorter than the SnCh b bonds.…”
Section: Resultsmentioning
confidence: 97%
“…Compound 1 crystallizes in the monoclinic space group P 2 1 / c with 4 formula units per unit cell. The bond lengths and angles within the trigonal bipyramidal [Pb 2 Se 3 ] 2– anion are similar to those in [K([2.2.2]crypt)] 2 [Pb 2 Se 3 ]10 (values given in parenthesis): Pb–Pb 3.2194(6) Å [cf. 3.2260(8) Å], Pb–Se 2.7366(14)–2.7842(12) Å [cf.…”
Section: Resultsmentioning
confidence: 55%
“… Reaction pathways for the oligomerization of en , as reported10 or observed herein (see Figure S1 and Table S2, Supporting Information). …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations